2019
DOI: 10.1093/braincomms/fcz047
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of methods for assessing polygenic burden on Alzheimer’s disease pathology and risk beyond APOE

Abstract: Genome-wide association studies have identified dozens of loci that alter the risk to develop Alzheimer’s disease. However, with the exception of the APOE-ε4 allele, most variants bear only little individual effect and have, therefore, limited diagnostic and prognostic value. Polygenic risk scores aim to collate the disease risk distributed across the genome in a single score. Recent works have demonstrated that polygenic risk scores designed for Alzheimer’s disease are predictive of clinical diagnosis, pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
97
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(103 citation statements)
references
References 46 publications
5
97
1
Order By: Relevance
“…Possible explanations are differences in diagnostic/disease stage, and sometimes also differences in genetic variants included in the PRSs. Importantly, our results in plasma replicate a previous report in CSF within the same cohort [ 16 ]. Moreover, we included three versions of PRSs and they performed relatively similar.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Possible explanations are differences in diagnostic/disease stage, and sometimes also differences in genetic variants included in the PRSs. Importantly, our results in plasma replicate a previous report in CSF within the same cohort [ 16 ]. Moreover, we included three versions of PRSs and they performed relatively similar.…”
Section: Discussionsupporting
confidence: 91%
“…So far, studies of the relation between AD-PRSs and plasma p-tau181 are lacking. Previous CSF-based results of most relevance for comparison with our plasma-based results are those presented in a recent study of polygenic burden on AD pathology in ADNI [ 16 ]. Similar to our finding, the authors reported that CSF p-tau181 was independently (after correction for APOE ) associated with the 31-SNP polygenic hazard score (PHS) (including APOE effects) used in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The papers we have published so far cover a broad range of topics in neurology, psychiatry and neuroscience from cell and animal models of diseases to human cohort studies. The new cover figure for volume 2 comes from Altmann et al (2019) who have found that polygenic risk score excluding the APOE4 locus associates with clinical diagnosis and biomarkers. The images show regional associations between amyloid PET tracer uptake and polygenic risk scores in the Alzheimer’s Disease Neuroimaging Initiative cohorts.…”
mentioning
confidence: 99%